2022
DOI: 10.1055/a-1846-1025
|View full text |Cite
|
Sign up to set email alerts
|

Bite-on-bite biopsies for the detection of residual esophageal cancer after neoadjuvant chemoradiotherapy

Abstract: Background Active surveillance after neoadjuvant treatment is increasingly implemented. The success of this strategy relies on the accurate detection of residual cancer. This study aimed to assess the diagnostic value of a second (bite-on-bite) biopsy for the detection of residual esophageal cancer and to correlate outcomes to the distribution of residual cancer found in the resection specimen. Methods A multicenter prospective study of esophageal cancer patients undergoing active surveillance aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A bite-on-bite biopsy strategy was implemented in this trial in attempts to improve diagnostic yield by obtaining tissue samples beyond the mucosa. While the use of bite-on-bite biopsy was reported to have decreased the rate of false negative biopsies from 31% to 11%, a separate trial by the Netherlands group on using biopsies from the SANO trial 29 showed that the improved residual tumor detection was due to an increased number of samples taken rather than the depth of the biopsy. Nevertheless, the trial used a combination of endoscopic bite-on-bite biopsy, EUS, PET-CT imaging, and a two-stage clinical response system (Figure 2) to assess the presence of residual tumor based on tumor response.…”
Section: Evaluation For Complete Responsementioning
confidence: 99%
“…A bite-on-bite biopsy strategy was implemented in this trial in attempts to improve diagnostic yield by obtaining tissue samples beyond the mucosa. While the use of bite-on-bite biopsy was reported to have decreased the rate of false negative biopsies from 31% to 11%, a separate trial by the Netherlands group on using biopsies from the SANO trial 29 showed that the improved residual tumor detection was due to an increased number of samples taken rather than the depth of the biopsy. Nevertheless, the trial used a combination of endoscopic bite-on-bite biopsy, EUS, PET-CT imaging, and a two-stage clinical response system (Figure 2) to assess the presence of residual tumor based on tumor response.…”
Section: Evaluation For Complete Responsementioning
confidence: 99%
“…[227][228][229] A recent study showed that the use of bite-on-bite biopsies delivers a 20% improvement in the detection of residual esophageal cancer. 230 A separate study (preSINO) is ongoing, and will determine the accuracy of radiographic and endoscopic evaluation of clinical complete response in squamous cell esophageal cancer. 231 Alternative and augmentative approaches have also been studied, including through the use of a non-endoscopic sponge and endoscopic response evaluation guided by artificial intelligence.…”
Section: Ongoing Surgical Trialsmentioning
confidence: 99%